Shakespeare and the Victorians - Sillars, Stuart, 1951- (Oxford Shakespeare topics., 2013)
OXFORD SHAKESPEARE TOPICS General Editors: Peter Holland and Stanley Wells Oxford Shakespeare Topics provide students and teachers with short books on important aspects of Shakespeare criticism and scholarship. Each book is written by an authority in its field, and combines accessible style with original discussion of its subject. The book shows how the reception and remodelling of the works and the man directed the Victorian construction of identity, personal, national and aesthetic, as well as laying foundations that later Shakespeareans could continue, extend or reject. Shakespeare was one of the most pervasive intellectual, aesthetic, and social forces of the Victorian period, with the plays in print, performance, and as moral examples penetrating to every aspect of life in every social class and situation. Shakespeare and the Victorians offers an analytical survey of the main forms and paths of this presence. It begins with a discussion of the processes of editing and publishing the plays, embracing both cholarly and popular editions. It moves toconsider performance styles, quoting original reviews to assess methods of acting and production. Music for the Shakespearean stage, now largely forgotten, is reassessed, as is the varied tradition of Shakespeare painting that extends far beyond the familiar images of the Pre-Raphaelites. Shakespearian themesdominate in the novel, especially the conflict between town and country and the changing status of women; poetry shows the power of Shakespeare in the use of iambic pentameter and the sonnet form. The plays are fragmented through the study of individual character and their use as moral compendia, and the search for 'Shakespeare the man' in biographies, portraiture and pilgrimages to the birthplace. A concluding chapter looks at the last two decades in terms of editing, performance, the.